Herd health survey on acaricide use practices among dairy farmers in Kenya - Maina, Kevin; Parlasca, Martin; Rao, E.J.O (2025)
Original household survey data collected between October-November 2023 from dairy farmers in Kenya in three counties (Elgeyo-Marakwet, Uasin Gishu and Nandi) collected to understand acaricide use and its environmental implications. The total sample size is 578 farmers selected using a multistage random sampling. The data contains household and farm characteristics, acaricides products used and application practices. The data can be used for replication studies.